Complex geophysical investigation of the Kapušany landslide (Eastern Slovakia) - KUŠNIRÁK, David; DOSTÁL, Ivan; PUTIŠKA, René; MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2016)
Geophysical survey is a very useful and popular tool used by engineering geologists to examine landslides. We present a case study from the Kapušany landslide, Eastern Slovakia, where a broad spectrum of geophysical methods were applied along two perpendicular profiles in order to compare the ability of the methods to detect as many structural features of the landslide as possible. The 2D Electrical Resistivity Tomography inverse model was capable of defining the geological structure of the landslide and defining the shear zone, however the resolution of the inverse model does not allow us to identify cracks or other minor features of the landslide. These, however, were well recorded in the results of Dipole Electromagnetic Imaging and the Self Potential method. In addition microgravimetry, Gamma-Ray Spectrometry and Soil Radon Emanometry were experimentally employed to validate the results obtained from electrical methods and afterwards final geological models, based on the integrated interpretation of all involved methods were constructed.